Digitalization of Village Administration to Improve Public Service Efficiency in Waiheru Village, Baguala District, Ambon City - SAKIR, Ahmad Rosandi; Almahdali, Humairah; NORMAWATI, Normawati (PT Batara Swastika Harati, 2025)
This Community Service activity focuses on the digitalization of village administration in Waiheru Village, Baguala District, Ambon City, to enhance public service efficiency. Through digitalization, village administrative processes are expected to become faster, more transparent, and more accurate. The implementation of digital systems enables the community to access public services online, reducing reliance on manual systems that are slow and prone to data errors. However, the digitalization process faces several challenges, including limited technological infrastructure, low digital literacy among village officials, and the digital divide within the community. Proposed solutions include digital literacy training, technological infrastructure enhancement, and public outreach initiatives. The expected outcomes include increased community participation in public services, improved accountability, and greater transparency at the village level. This digitalization effort is envisioned as a model for other villages, fostering a more efficient and responsive village governance system that meets the needs of its residents.